A numerical study on the effect of dust particles on tritium deposition on plasma-facing materials. (June 2022) - Niu, Guo-Jian; Kawamura, Gakushi; Xu, Qian; He, Tao; Nian, Fei-Fei; Wang, Rong; Yang, Zhong-Shi; Luo, Guang-Nan
Abstract: Tritium deposition is a key issue for fusion devices. The existence of dust leads to increase of tritium deposition rates due to the large specific surface area (SSA) of dust grains. Experiments in JET-ILW have indicated that the deposition and retention behavior of hydrogen on dust grains is complicated. In present work, the deposition behavior of tritium on the dust is studied by a hybrid particle simulation method. Our results indicate that the large SSA of dust is not the only mechanism that increases tritium deposition. Dust size and the electrostatic sheath induced by the dust are also important factors that influence the tritium deposition. The retention rate enhanced by dust grains is also predicted based on our study. Highlights: The electrostatic sheath plays an important role in tritium deposition on dust. The ion deposition mechanisms are different for different size dust grains. A model is built to illustrate the mechanisms of tritium deposition on dust grains.